Education and Process of Inclusion Under Neo-liberal Political Economy. Issue 2 (December 2018) - Shah, Ghanshyam
Abstract: Theoretically, modern formal education develops not only critical questioning mind and skills but also inculcates universalistic values leading to humane social relationships. For attaining such objective, the education system needs to evolve institutions, curricula, competent committed teachers and pedagogies. Though the architects of the Indian Constitution and the First Education Commission emphasised importance of education for national integration, and egalitarian secular social order, rigorous institutional mechanism, modules and pedagogies have not developed in the last six decades to attain the objective. This has not been on political agenda. Education policy and governance have been lopsided and piecemeal. Colonial educational ethos has continued. Education has spread widely across all social strata with increasing enrolment at all levels; the system segregates and discriminates students from the primary stage. Only miniscule section of society gets good quality education enabling them to occupy higher positions in different sectors. The system has failed in inculcating plural secular egalitarian values. Hegemonic values of dominant strata embedded in hierarchical ethos are reinforced and legitimised.